ANALISIS PENGARUH VARIABEL EKONOMI MAKRO TERHADAP BESARNYA JUMLAH PENERIMAAN ZAKAT DI BADAN AMIL ZAKAT NASIONAL (BAZNAS) PUSAT TAHUN 2014 – 2018 - Anggi Irawan (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2021)
Indonesia actually has very big zakat potensial reaching 217 trilion rupiah. This huge potential is equivalent to 3.4% of Indonesia’s GDP in 2010. The large potential of zakat can be a solution to overcome poverty in Indonesia. One of the factors that influence zakat receipt in indonesia is the macroeconomic factor. However, this potential still tends not to have a positive impact on the macro economy and overall poverty reduction in Indonesia. This study aims to examine the impact of macroeconomic factors in the form of inflation, BI-Rate, Profit sharing ratio,exchange rate and the amount of money in circulation against zakat receipts in the Central national amil zakat agency (BAZNAS). This research is quantitative using secondary data. The data used are sourced from BAZNAS, Bank Indonesia and the Financial Services Authority (OJK) from 2014-2018. Data were analyzed using multiple linear regression. The result of this study indicate that simultaneously, inflation, BI Rate, profit sharing ratio, exchange rate and the amount of money in circulation (M2) have an effect on the amount of zakat receipts in Indonesia. But partially, the ratio for the result is not affects the amount of zakat receipts in Indonesia. In contras to inflamation, the BI-Rate and exchanged rate has a negative and significant effect. Meanwhile, the amount of money in circulation has a positive and significant effect on zakat aceptance in the central national amil zakat agency (BAZNAS) 2014-2018.